Animal-assisted interventions as innovative tools for mental health - Francesca Cirulli; Marta Borgi; Alessandra Berry; Nadia Francia; Enrico Alleva (Istituto Superiore di Sanità, 2011)
There is a growing interest for the potential health benefits of human-animal interactions. Although scientific evidence on the effects is far from being consistent, companion animals are used with a large number of human subjects, ranging from children to elderly people, who benefit most from emotional support. Based on a comprehensive review of the literature, this paper examines the potential for domesticated animals, such as dogs, for providing emotional and physical opportunities to enrich the lives of many frail subjects. In particular, we focus on innovative interventions, including the potential use of dogs to improve the life of emotionally-impaired children, such as those affected by autism spectrum disorders. Overall an ever increasing research effort is needed to search for the mechanism that lie behind the human-animal bond as well as to provide standardized methodologies for a cautious and effective use of animal-assisted interventions.